(untitled) (Research, Society and Development, 2020)
This work aims to analyze the school parties held by Senador Guerra School Group, located in Caicó/RN, between the years 1940 and 1946, a period known in Brazilian political history as Era Vargas. The documentation cataloged in the documentary collection of this institution records that at that time celebrations were held for the Brazilian Youth Day, Children’s Day, Race Day and President Getúlio Vargas’ Birthday Day. These events were supervised and supervised by the Press and Propaganda Department (DIP) created by President Getúlio Vargas in 1939. The documentary sources used include newspaper articles, Government Messages, Laws and Decrees, as well as school documents such as the Events of the Senador Guerra School Group (1937-1949). In the case of a historical investigation based on the perspective of Cultural History, we list authors such as Burke (1992), Chartier (1990), Certeau (2012), Morais (2006) and Souza (1998) in an attempt to extract methodological subsidies to support this article. When researching school parties held by the institution under analysis, we aim to expose the insertion of the school community of Seridó norte-rio-grandense in the political and cultural context that characterized Brazil during the Era Vargas. We note the importance of these events for the moral and civic education of students in Caico, since they exceeded the physical limits of the classrooms and were implemented in public spaces such as squares and streets that served as a stage for the dissemination of educational practices, norms and values.